Peran Vital Ultrasonografi Dupleks pada Fistula Arteriovenosa sebagai Akses Hemodialisis - Firdaus, Achmad Jauhar; Kurnianingsih, Novi (RSUD Dr. Saiful Anwar Province of East Java, 2024)
The global incidence of end-stage renal disease (ESRD) is rising, amounting to more than 800 million individuals are suffered, in line with the rise of the number of patients undergoing hemodialysis as treatment modalities. Hemodialysis requires vascular access, and the arteriovenous fistula (AVF) access is considered the most ideal vascular access option due to its long-term patency and low complication rate compared to other access options. However, up to one-third of hospital admissions for ESRD patients are caused by AVF dysfunction, which is also one of the main causes of morbidity and mortality in ESRD patients. AVF creation requires careful pre- and post-operative evaluation to ensure the vascular access maturation and patency. While the latest guidelines have not explicitly emphasized the role of vascular mapping and surveillance, routine duplex ultrasonography before and after AVF creation procedures holds great potential advantages to ensure the success of AV access for hemodialysis.